Literature Review: Analysis of K3 Implementation in Textile Industry Companies - Nurhasanah, Siti Aldina (Jurnal Pengabdian Nusantara, 2024)
Occupational Safety and Health (K3) has a crucial role in projects with a high risk of work accidents. Non-compliance with the implementation of the Occupational Health and Safety Management System (SMK3) can have serious impacts on humanitarian, economic, environmental, and legal aspects. The close relationship between workers and work accidents has an impact on productivity, making the application of SMK3 an important factor in human resource development. SMK3 not only protects workers in the company, but also involves protecting the community from the dangers caused by industrial products. The risk of hazards in the work environment can hamper worker safety and health conditions, reduce efficiency, and interfere with organizational effectiveness. Law Number 1 of 1970 regulates the implementation of K3 in all workplaces in Indonesia, including land, in the ground, on the surface of the water, in the water, and in the air. SMK3 is the most important part in the risk management of a company or organization. In an effort to form an effective SMK3, companies need to internalize awareness of the importance of K3 and provide education to employees about safety and health in the workplace. Work accident cases can cause worker suffering, decreased production, and financial losses for the company. This study conducted a literature review on the application of K3 in the textile industry. This research method is literature review with a qualitative approach. Data obtained from scientific articles/journals using Google Scholar with the keyword "implementation of SMK3 in Textile Industry Plantations". The screening results resulted in 3 articles being analyzed. The conclusion of the literature review shows that textile companies comply with the national policy of K3 and develop internal guidelines in accordance with regulations. Hazard risk identification and risk assessment are carried out to prevent accidents. The relationship of the physical work environment with work accidents was indicated in the study. Regular training and supervision of the use of Personal Protective Equipment (PPE) demonstrates the company's commitment to safety. Periodic safety evaluations are also carried out to continuously improve safety standards. In the context of the textile industry, the implementation of K3 is not only a legal necessity, but also an investment in worker welfare, productivity, and company reputation. By involving workers in safety decisions, providing training, and continuously conducting evaluations, companies can achieve a safe work environment and support human resource development.